Primary selection into shift work and change of cardiovascular risk profile - Mei Yong; Christina Germann; Stefan Lang; Christoph Oberlinner (Nordic Association of Occupational Safety and Health (NOROSH), 2015)
OBJECTIVES: A potential "healthy shift worker effect" may bias the studied effect of shift work on health. The observed differences among shift and day workers in health behavior and health outcomes can be caused by: (i) primary selection, (ii) the influence from the shift work-related environment, and (iii) the impact of shift work. We aimed to study these potential sources. METHODS: A cohort of 4754 male trainees who had finished their professional training and started their career in production in a chemical company between 1995 and 2012 was identified. Among them, 1348 (28%) were involved in rotating shift work and 3406 (72%) in day work. Information on health behavior and risk factors for cardiovascular diseases was retrieved from the medical examinations. This information was then compared (i) at the beginning of training, (ii) at the end of training, and (iii) 3 years after the employment, in relation to the working time. RESULTS: At the beginning of the training, the prevalence of smokers was higher among future shift workers (26% versus 21%), from 1995 to 2012. During the training and the first three years of employment, a marginal decline of systolic blood pressure and an elevation of triglyceride were related with shift work. No difference was found with respect to other risk factors for cardiovascular diseases. CONCLUSIONS: Our findings do not support a primary selection in favor of shift workers. An impact of shift work on the risk profile of cardiovascular diseases was not indicated in the observation period.